Water pollution remediation: Synthesis, characterization and adsorption studies of poly(o-anisidine)/MWCNTs nanocomposite for the elimination of direct yellow 26 dye (Kuwait Journal of Science)
The synthesis of poly(o-anisidine)/multi-walled carbon nanotubes composite (POA/MWCNTs NC) was carried out via chemical oxidative polymerization for the adsorptive removal of Direct Yellow 26 dye (DY 26). In the polymerization, the ammonium persulphate was used as an oxidant along with 4,4′-diaminodiphenylamine dimer as initiator. Then, the structural composition, crystalline properties, absorption behavior, morphology, and surface attributes of both the polymer and the nanocomposite were analyzed by different techniques such as Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), UV–visible spectroscopy (UV–visible), scanning electron microscopy (SEM) and Brunauer-Emmett-Teller analysis (BET). BET analysis showed significant improvement in the surface area (690 m2/g) and porosity (0.216 cm3/g) of the composite material as compared to pure POA. Further, the composite was applied for the elimination of DY 26 in aqueous media. Moreover, the adsorption parameters were also optimized like pH, contact time, adsorbent dose and dye concentration. The highest dye removal efficiency was achieved up to 83% against 50 mg/L concentration of dye solution under the conditions of pH at 2, contact time of 30 min, and 2 g amount of the adsorbent. Furthermore, the kinetic studies revealed that the adsorption of DY 26 followed the pseudo first-order rate constant by the polymeric adsorbent. © 2025